PENGELOLAAN FASILITAS OBJEK WISATA THE JOGLO GARDEN MINI ZOO DI KECAMATAN JATISAMPURNA, KOTA BEKASI - Luthfi Himawan Afari; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The Joglo Garden Mini Zoo is one of the attractions in the form of a zoo located in Jatisampurna District, Bekasi City. This zoo has various facilities that can attract tourists. It takes good management and maintenance to increase tourist visits. management is a series of processes in the form of planning, organizing, controlling and supervising in an organization, especially in the world of education so that the desired educational goals can run effectively and efficiently. This research was conducted to find out how the management of facilities at the Joglo Garden Mini Zoo tourist attraction in Jatisampurna District, Bekasi City. This study uses qualitative methods with data collection techniques in the form of observation, interviews, and documentation. Based on the results of research on the Management of Tourism Object Facilities The Joglo Garden Mini Zoo in Jatisampurna District, Bekasi City is in a fairly good category. Keywords : Management, Facilities, Zoo